Financial Deepening Impacts on Regional Economic Growth - Harisuddin Harisuddin; Djoni Hartono (Faculty of Economic and Business Syarif Hidayatullah State Islamic University of Jakarta, 2019)
The impacts of financial deepening on economic growth have been a debate for decades. This research analyzes the impacts of financial deepening on provincial-level economic growth in Indonesia from 2001 to 2016. The use of provincial level data is rarely found in the literature, as well as to reduce unobserved heterogeneity in cross-sectional data between countries. The financial deepening approach in this study is limited to the banking side considering that the banking sector is still very dominant compared to other financial sectors in Indonesia. Through the panel data approach, it found there is a significant positive correlation between financial deepening and regional economic growth supporting previous studies. In this regard, the Government must take serious steps to deepen the domestic financial market, primarily through the banking sector.